Regulation and roles of FOXK2 in cancer - Kang, Yuanyuan; Zhang, Kexin; Sun, Lixue; Zhang, Ying (Frontiers in Oncology, 2022)
Forkhead box K2 (FOXK2) is a member of the forkhead box transcription factor family that contains an evolutionarily conserved winged-helix DNA-binding domain. Recently, an increasing number of studies have demonstrated that FOXK2 plays an important role in the transcriptional regulation of cancer. Here, we provide an overview of the mechanisms underlying the regulation of FOXK2 expression and function, and discuss the roles of FOXK2 in tumor pathogenesis. Additionally, we evaluated the prognostic value of FOXK2 expression in patients with various cancers. This review presents an overview of the different roles of FOXK2 in tumorigenesis, and will help inform the design of experimental studies involving FOXK2. Ultimately, the information presented herein will help to enhance the therapeutic potential of FOXK2 as a cancer target.